Superselective Renal Artery Embolization Management of Post-percutaneous Nephrolithotomy Hemorrhage and Its Methods - Dong, Xiangjun; Ren, Yanqiao; Han, Ping; Chen, Lei; Sun, Tao; Su, Yangbo; Feng, Yiming; Ma, Jinqiang; Liang, Huimin; Zheng, Chuansheng (Frontiers in Surgery, 2020)
Objective: The purpose of this study was to evaluate the therapeutic efficacy and safety of superselective renal arterial embolization (SRAE) in the treatment of patients with renal hemorrhage after percutaneous nephroscopy (PCNL). In addition, embolization techniques and embolization materials during operation were also worthy of further discussion. Methods: From February 2015 to December 2019, clinical data of 49 consecutive patients with renal hemorrhage after PCNL were retrospectively analyzed. Demographic and clinical data of patients were recorded, changes in serum creatinine values were analyzed, and the safety and efficacy of TAE were evaluated. Clinical experience was also recorded. Results: A total of 49 patients underwent angiography, of which 46 patients received SRAE due to positive hemorrhagic foci detected by angiography, and the technical success rate of 46 patients was 100%. Among the 3 patients who did not receive embolization, 1 patient underwent nephrectomy and 2 patients improved with conservative treatment, with a clinical success rate of 98%. There was no statistically significant difference between serum creatinine before PCNL and 7 days after SRAE (101.6±36.5μmol/L to 100.5±27.1 μmol/L; P= 0.634), and no significant change was observed in serum creatinine at the last follow-up (99.4±34 μmol/L, P=0.076). No major complications occurred after embolization. Conclusions: SRAE is safe and effective in patients with renal hemorrhage after PCNL. The experience of interventional therapy and the choice of embolization materials in this study may provide certain benefits for the treatment of patients with renal hemorrhage after PCNL.